Absence of γ‐aminobutyric acid‐a receptor potentiation in central hypersomnolence disorders. Issue 2 (14th July 2016) - Dauvilliers, Yves; Evangelista, Elisa; Lopez, Regis; Barateau, Lucie; Jaussent, Isabelle; Cens, Thierry; Rousset, Matthieu; Charnet, Pierre
Abstract : Objective: The pathophysiology of idiopathic hypersomnia (IH) remains unclear. Recently, cerebrospinal fluid (CSF)‐induced enhancement of γ‐aminobutyric acid (GABA)‐A receptor activity was found in patients with IH compared to controls. Methods: Fifteen unrelated patients (2 males and 13 females) affected with typical IH, 12 patients (9 males and 3 females) with narcolepsy type 1, and 15 controls (9 males and 6 females) with unspecified hypersomnolence (n = 7) and miscellaneous neurological conditions (n = 8) were included. A lumbar puncture was performed in all participants to measure CSF hypocretin‐1 and GABA‐A response. We used a voltage‐clamp assay on Xenopus oocytes injected with the RNAs that encode the α1 β2 γ2 or the α2 β2 γ2 subunits of the human GABA‐A receptor. A sequence of 6 different applications (GABA, GABA/CSF, and CSF alone) with 2 to 4 oocytes per CSF sample was performed in a whole‐cell voltage‐clamp assay. Results: Representative current traces from oocytes expressing human α1 β2 γ2 or α2 β2 γ2 GABA‐A receptors were recorded in response to 6 successive puffs of GABA diluted in the survival medium (SM), showing stable and reliable response. GABA puffs diluted in SM/CSF solution or SM/CSF solution alone showed no significant differences in the CSF of IH, narcolepsy, or control groups. No associations were found between GABA responses, demographic features, disease duration, or disease severity in the whole population or within groups. Interpretation: Using the Xenopus oocyte assay, we found an absence of GABA‐A receptor potentiation with CSF from patients with central hypersomnolence disorders, with no significant differences between hypocretin‐deficient and non–hypocretin‐deficient patients compared to controls. Ann Neurol 2016;80:259–268